Oral health attitudes and behavior among a group of female Saudi dental students - Mohammad Abdul Baseer; Ghousia Rahman (Wolters Kluwer Medknow Publications, 2014)
Aim: Aim of the present study was to evaluate the oral health attitudes and behavior of female undergraduate dental students in Kingdom of Saudi Arabia, according to age and level of dental education. Materials and Methods: A self-administered questionnaire based on the Hiroshima University - Dental Behavior Inventory (HU-DBI) was distributed among 351 dental students at Riyadh colleges of dentistry and pharmacy. Results: A response rate of 88% was obtained. The mean HU-DBI score did not show any significant relationship (P < 0.05) with age and academic level dental education by one way-analysis of variance (ANOVA). The students were considerably concerned about the appearance of their teeth and gums and halitosis. The total mean score was not markedly higher in the clinical levels (level 7 to level 12) than in the non-clinical levels (level 1 to level 6), indicating that the students were almost equally aware. The present study showed that dental students in Saudi Arabia had poor oral health awareness. Conclusion: The oral health behavior of Saudi dental students needs to be improved in order to serve as a positive model for their patients and the community.